New observations of two rare rallids (Aves: Gruiformes: Rallidae) on Hispaniola - Miguel A. Landestoy T. (Novitates Caribaea, 2017)
The Yellow-breasted Crake, Hapalocrex flaviventer (Boddaert, 1783), and the Spotted Rail, Pardirallus maculatus (Boddaert, 1783), are rarely reported and poorly known birds on Hispaniola. Of the first species there were no recent records, while for the second, the range of distribution is significantly expanded based on new observations, which are chronologically summarized in order to assess the possibility of breeding in the island. Some rarely reported aspects of the latter species’ behavior are commented. The habitat is generally characterized in at least one locality where both species are syntopic.